Consumo e digestibilidade aparente de fenos de Brachiaria Decumbens, stapf cultivar brasiliski cortados em tres diferentes idades - Matheus Anchieta Ramirez (2010)
The aim of this experiment was to evaluate the voluntary intake and digestibility of dry matter, crude protein, fibrous fractions, energy and nitrogen balance of Brachiaria decumbens hay made from the plant cut into three ages, 56, 84 and 112 days. The statistical design was completely randomized design with three treatments and six replications. There were no differences (p> 0,05) for hay obtained with plants grown at56, 84 and 112 days for the values of dry matter intake, 65,60, 60,37 and 57,66 g / MBW / day , consumption of organic matter, 61,03, 56,48 and 53,98 g / MBW / day, and consumption of crude energy, 283,96, 265,69 and 249,85 kcal / MBW / day. Apparent digestibility of dry matter and organic matter to the hays obtained with plants grown at 56 and 84 days respectively 55,96 and 55,68% for dry matter and 58,09 and 57,94% for organic matter, were similar to each other (p> 0,05) and higher than thevalue of hay to 112 days, 45,61% for dry matter and 48,66% for organic matter (p <0,05). The apparent digestibility of crude energy followed the same logic with values of 55,85 and 53,98% for hay at 56 and 84 days similar (p> 0,05) and higher than the value of 45,79 % for hay for 112 days (p <0,05). For the intake of NDF, ADF, cellulose, and digestibility of ADF and cellulose were similar among the three cut (p> 0,05). The values of digestibility of NDF and consumption of lignin were similar among therelevant hays 56 and 84 days (p> 0,05) and greater than the hay 112 days (p <0,05). The consumption of hemicelluloses was higher for hay for 56 days (p <0,05) than the hay at 84 and 112 days, which were similar, since the value of the digestibility of hemicelluloses for the age of 56 days was higher that of the age of 84 days (p <0,05), which was higher than the age of 112 days (p <0,05). The consumption of crude protein hay obtained from this plant for 56 days, 4,53 g / MBW / day, was higher (p <0,05) thanthe one presented for hay 84 days, 3,58 g / MBW / day which in turn has been greater (p <0,05) than the hay for 112 days, 2,54 g / MW / day. Aprarent digestibility of crude protein values obtained with the hay harvested from plants at 56 and 84 days were similar (p>0,05) between 42,25 and 37,67%, and higher (p<0,05) that the value obtained with hay for 112 days, 2,86%. For the nitrogen balance values followed the same logic with similar values found for the age of 56 and 84 days, 1.97 and 0.86 g / day (p> 0,05) and higher than the value of -1,95 g / day for 112 days of age (p <0,05). The values of voluntary intake and digestibility indicate the ages of 56 and 84 days as similar and above the age of 112 days for making hay from Brachiaria decumbens